A Novel “Y” Stent Flow Diversion Technique for the Endovascular Treatment of Bifurcation Aneurysms without Endosaccular Coiling - Cekirge, H.S.; Yavuz, K.; Geyik, S.; Saatci, I. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Stent-assisted endovascular treatment and flow diversion techniques are increasingly used for the management of wide-neck intracranial aneurysms. We report our initial clinical experience using a new flow diversion technique for the endovascular management of bifurcation aneurysms. MATERIALS AND METHODS: Eight bifurcation aneurysms were treated by placing 2 stents in Y-configuration with no accompanying endosaccular packing. This treatment technique aimed at flow diversion was selected in these cases because 1) the aneurysm was giant and causing mass effect, 2) the emanating branches were incorporated within the sac, or 3) the aneurysm was too small. Aneurysms were located at middle cerebral (5 aneurysms) and basilar artery bifurcations (3 aneurysms). Five aneurysms were small, 1 was large, and 2 were partially thrombosed giant. Closed-cell stents were used in all Y-stent placement procedures. RESULTS: In all aneurysms, both stents could be placed at the intended locations without any procedural complication. Follow-up angiograms obtained at 3 months to 2 years demonstrated that all stents were patent except for one with asymptomatic P1 occlusion. Complete occlusion with remodelled bifurcation was observed in all middle cerebral artery bifurcation aneurysms and the large basilar tip aneurysm. Residual filling despite reduction in size was observed in both of the partially thrombosed giant aneurysms at 2-year and 3-month follow-up angiograms, respectively. CONCLUSIONS: Flow diversion with double stent placement in Y-configuration provided successful and stable aneurysm occlusion. The technical and clinical results achieved are highly encouraging that this technique may contribute to the endovascular treatment of these complex bifurcation aneurysms. CTACT angiographyDSAdigital subtraction angiographyICAinternal carotid arteryMCAmiddle cerebral arteryPCAposterior cerebral arteryPcomAposterior communicating arteryRrupturedSAHsubarachnoid hemorrhageSCAsuperior cerebellar arteryUunrupturedVAvertebral artery